ASSOCIATION OF DIGITAL LITERACY AND CRITICAL THINKING SKILLS IN JUNIOR HIGH SCHOOL STUDENTS - Umi Haniati; Rahmat Iqbal; Muhammad Amin Choso (2025)
The rapid development of digital technology has significantly transformed various aspects of education, emphasizing the need for students to not only access but also critically evaluate and ethically use information. Digital literacy has thus become a key 21st-century competency. Simultaneously, critical thinking—encompassing interpretation, analysis, evaluation, inference, and explanation—is crucial for navigating the complexities of the digital age. This study investigates the relationship between digital literacy and critical thinking skills among junior high school students in Purbalingga, Indonesia. Using a quantitative correlational approach, data were collected from 92 students through Likert-scale questionnaires based on the frameworks of Hinrichsen & Coombs (2013) for digital literacy and Facione (1990) for critical thinking. The validity and reliability of the instruments were confirmed through Pearson's correlation and Cronbach's Alpha tests, respectively. The results revealed a strong and statistically significant correlation (r = 0.623; p < 0.01) between digital literacy and critical thinking. Each dimension of digital literacy—information access, evaluation, communication, collaboration, and creativity—was positively associated with various dimensions of critical thinking. These findings suggest that digital literacy practices inherently contribute to developing students' higher-order thinking skills. The study highlights the importance of integrating comprehensive digital literacy education into school curricula to enhance technical competencies and foster critical cognitive abilities necessary for informed digital citizenship. This research provides empirical support for curriculum development that aligns with the demands of digital transformation in education.